Functional Tax Governance Apparatus and Economic Development - ADEUSI Amos Sunday; Dr. OLADELE, Rotimi (International Journal of Engineering and Management Research, 2018)
The proportion of tax earnings to gross domestic product (GDP) in Nigerian economy had been ranked and affirmed the least in the sub-Sahara African and as evolving economy, different reasons attested to this fact, hence, the study is aimed at investigate the inherent lacuna of tax governance apparatus in responses to economic development as broad objective. The study employed field research design, the research instrument that was deployed for collection of data is purposive and structured questionnaire targeted at elicit information from relevant and related stakeholders in tax matters, the research instrument and data collected were subjected to Cronbach alpha test and heteroscedasticity test to affirm the validity/reliability and best linear unbiased estimator of data collected respectively. The result revealed that the responsiveness of economic development to tax assessment, tax policy and tax administration were statistically significant inversely related while tax collection was statistically insignificant related directly with economic development. Thereby study concluded that poor management and administration of tax system in Nigeria responsible for adverse relationship that subsist between the proportion of tax earnings to GDP and resulted decayed and declined physical infrastructures and socio-